IDH Mutations: Genotype-Phenotype Correlation and Prognostic Impact. (30th April 2014) - Wang, Xiao-Wei; Ciccarino, Pietro; Rossetto, Marta; Boisselier, Blandine; Marie, Yannick; Desestret, Virginie; Gleize, Vincent; Mokhtari, Karima; Sanson, Marc; Labussière, Marianne
Abstract : IDH1/2 mutation is the most frequent genomic alteration found in gliomas, affecting 40% of these tumors and is one of the earliest alterations occurring in gliomagenesis. We investigated a series of 1305 gliomas and showed that IDH mutation is almost constant in 1p19q codeleted tumors. We found that the distribution of IDH1 R132H, IDH1 nonR132H, and IDH2 mutations differed between astrocytic, mixed, and oligodendroglial tumors, with an overrepresentation of IDH2 mutations in oligodendroglial phenotype and an overrepresentation of IDH1 nonR132H in astrocytic tumors. We stratified grade II and grade III gliomas according to the codeletion of 1p19q and IDH mutation to define three distinct prognostic subgroups: 1p19q and IDH mutated, IDH mutated—which contains mostly TP53 mutated tumors, and none of these alterations. We confirmed that IDH mutation with a hazard ratio = 0.358 is an independent prognostic factor of good outcome. These data refine current knowledge on IDH mutation prognostic impact and genotype-phenotype associations.